Relationship between Cigarette Smoking and Blood Pressure in Adults in Nepal - Basnet, Kapil (Nepalese Journal of Business, 2025)
This study examines the relationship between cigarette smoking and blood pressure in adults in Nepal. Blood pressure is selected as the dependent variable. Similarly, friend’s circles, stress, celebrity effect, interest, and social media are selected as independent variables. The study is based on primary data with 128 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing relationship between cigarette smoking and blood pressure in adults in Nepal. The study showed that stress has a positive impact on blood pressure. It means that an increase in stress leads to increase in blood pressure among adults. Similarly, friend’s circles has a positive impact on blood pressure. It indicates that bad friend’s circles motivate to smoking which leads to increase in blood pressure among adults. Likewise, celebrity effect has a positive impact on blood pressure. It means that increase in celebrity influence for smoking leads to increase in blood pressure among adults. Further, interest has a positive impact on blood pressure. It shows that an increase in smoking interest leads to increase in blood pressure among adults. In addition, social media has a positive impact on blood pressure. It shows that social media influence on smoking leads to increase in blood pressure among adults.